Critical systems thinking : a practitioner's guide. - Jackson, Michael C., 1951- (Wiley, 2024)
"Critical systems thinking is a multiperspectival and multimethodological approach to complex problems that takes advantage of the variety of systems approaches, aware of their different strengths and weaknesses"--